2018
DOI: 10.1016/j.neuron.2018.08.043
|View full text |Cite
|
Sign up to set email alerts
|

Distinct and Dynamic ON and OFF Neural Ensembles in the Prefrontal Cortex Code Social Exploration

Abstract: The medial prefrontal cortex (mPFC) is important for social behavior, but the mechanisms by which mPFC neurons code real-time social exploration remain largely unknown. Here, we utilized miniScopes to record calcium activities from hundreds of excitatory neurons in the mPFC while mice freely explored restrained social targets, in the absence or presence of the psychedelic drug phencyclidine (PCP). We identified distinct and dynamic ON and OFF neural ensembles that displayed opposing activities to code real-tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
120
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(140 citation statements)
references
References 70 publications
7
120
0
Order By: Relevance
“…We did not see any overall changes in firing rate, only weakly modulated touch and sex-touch neurons at both edges of a zero-centered distribution. While previous rodent studies did not investigate social touch as such, in line with our observations, it has been shown that during social approach (to a caged conspecific) prelimbic responses are weak and diverse 63,64 and that social behaviors are encoded by sparse groups of neurons either increasing or decreasing in activity during behavior ('on' and 'off' ensembles 65 ).…”
Section: Social Touch Responses In Frontal Cortexsupporting
confidence: 87%
“…We did not see any overall changes in firing rate, only weakly modulated touch and sex-touch neurons at both edges of a zero-centered distribution. While previous rodent studies did not investigate social touch as such, in line with our observations, it has been shown that during social approach (to a caged conspecific) prelimbic responses are weak and diverse 63,64 and that social behaviors are encoded by sparse groups of neurons either increasing or decreasing in activity during behavior ('on' and 'off' ensembles 65 ).…”
Section: Social Touch Responses In Frontal Cortexsupporting
confidence: 87%
“…Thus, imaging approaches can reveal how individual cells embedded in a larger network display coordinated activity during different stages of behavior or training (Wagner et al 2017;Heffley et al 2018;Galiñanes, Bonardi, and Huber 2018;Giovannucci et al 2017) . Moreover, because of their ability to record in freely moving animals, miniscopes have been instrumental in uncovering neural activity patterns occurring during natural behaviors and related brain-states including social interactions (Murugan et al 2017;Remedios et al 2017;Liang et al 2018;Kingsbury et al 2019) or sleep Cox, Pinto, and Dan 2016) with fully intact vestibular input.…”
Section: Introductionmentioning
confidence: 99%
“…Hippocampus, prefrontal cortex, and context representations. While we present the context-modular memory network as a generic architecture without explicit mention to brain areas and circuits, evidence suggests that contextual signals interact with cortical memories through the hippocampus, prefrontal cortex, and amygdala 1,13,[80][81][82][83][84] . For example, a recent study finds evidence of inhibitory control of cortical memories through the hippocampus 13 , providing direct support for a neuron-specific ( Fig.…”
Section: Circuit Motifs and Cell Types Involved In Gatingmentioning
confidence: 99%